Modelling Electronic Characteristic of InP/InGaAs Double Heterojunction Bipolar Transistor - Berrichi Yamina; Ghaffour Kherreddine (Institute of Advanced Engineering and Science, 2015)
In this paper, we are interested in studying InP/InGaAs heterojunction bipolar transistor NPN type. First and for most we should describe the structure of our simulation, then, we ploted at room temperature: Energy band diagram, Gummel plot, IC-VC characteristic and conduction bands for different values of VBE. The simulation of this structure has demonstrated the validity of our model and the method of the simulation.